2021
DOI: 10.12820/rbafs.26e0182
|View full text |Cite
|
Sign up to set email alerts
|

Promoting healthy lifestyles in Brazil: design and method of “VAMOS Program” in public health system

Abstract: The “Programa Vida Ativa Melhorando a Saúde – VAMOS” (Active Life Improving Health) is a community intervention with a behavioral approach. It uses educational strategies to assist health professionals in guiding the population about the importance of adherence and maintenance of healthy lifestyles. This descriptive study presents the design and method of the VAMOS Program version 2.0. The intervention is for adults and older adults’ users of Brazilian public health and aims to motivate them to adopt an active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…O VAMOS foi composto por 12 encontros com duração média de 60 a 90 minutos e em cada encontro foram distribuídos os livretos do programa gratuitamente para as idosas. Cada livreto abordava temas relacionados a atividade física, alimentação e como aderir a uma vida saudável (Benedetti et al, 2017;Tomicki et al, 2021). O profissional que conduziu o programa, denominado de multiplicador, foi certificado previamente por um treinamento on-line de 20 horas (José, Konrad, Ribeiro & Benedetti, 2019).…”
Section: Procedimentosunclassified
“…O VAMOS foi composto por 12 encontros com duração média de 60 a 90 minutos e em cada encontro foram distribuídos os livretos do programa gratuitamente para as idosas. Cada livreto abordava temas relacionados a atividade física, alimentação e como aderir a uma vida saudável (Benedetti et al, 2017;Tomicki et al, 2021). O profissional que conduziu o programa, denominado de multiplicador, foi certificado previamente por um treinamento on-line de 20 horas (José, Konrad, Ribeiro & Benedetti, 2019).…”
Section: Procedimentosunclassified
“…Health professionals invited the UBS users to participate in the VAMOS. Recruitment strategies have been described elsewhere (Tomicki et al, 2021). It should be noted that in each UBS the period of disclosure and screening occurs at different times.…”
Section: Recruitment Of Participantsmentioning
confidence: 99%
“…When it was impossible to be present at any meeting, it was suggested that the intervention leader replace the meeting. Details about the VAMOS, version 2.0, can be found in a previous study (Benedetti et al, 2017;Tomicki et al, 2021) and on the program's website: https://vamos.ufsc.br/.…”
Section: Vamos Program -Intervention Groupmentioning
confidence: 99%
See 2 more Smart Citations